2020
DOI: 10.1159/000509380
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aflibercept Treatment and Its Effect on the Retinal Perfusion in the Oxygen-Induced Retinopathy Mouse Model of Retinopathy of Prematurity

Abstract: Introduction: Bevacizumab and ranibizumab, which are anti-vascular endothelial growth factor (VEGF) medications, are used frequently in the treatment for retinopathy of prematurity (ROP) in infants. Aflibercept, or VEGF Trap, has been used anecdotally, but translation and clinical studies are lacking. Objective: This study investigates the efficacy of aflibercept at reducing areas of non-perfused retina and studies its effect on normal angiogenesis in the oxygen-induced retinopathy mouse model of ROP. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…1A ). Because expression of KH902 before P12 further dampens the development of the vasculature, and each vector serotype may exhibit different expression dynamics, we opted to quantify abnormal vascular growth by counting the number of aneurysms that form during the catch-up growth phase, rather than quantifying the area of normal vascularization, as has been done in other studies 45 , 46 , 48 ( Fig. 1B–D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ). Because expression of KH902 before P12 further dampens the development of the vasculature, and each vector serotype may exhibit different expression dynamics, we opted to quantify abnormal vascular growth by counting the number of aneurysms that form during the catch-up growth phase, rather than quantifying the area of normal vascularization, as has been done in other studies 45 , 46 , 48 ( Fig. 1B–D ).…”
Section: Resultsmentioning
confidence: 99%
“…The OIR of prematurity model is a well-established system for inducing abnormal vascular proliferation, which is characterized by a vascular catchup growth phase that is induced by a preceding hyperoxic phase during the development of the retinal vasculature 44 . Previous reports have shown that inhibition of VEGF during the catchup phase by conbercept 29 , or other anti-VEGF [45][46][47] drugs, reduces neovascular areas in the OIR mouse model. We thus compared the efficacy of rAAV2-and rAAV2.7m8-KH902 vectors in reducing neovascular pathologies in the OIR mouse model after intravitreal delivery.…”
Section: Kh902 Reduces the Number Of Aneurysms In The Oir Mouse Modelmentioning
confidence: 98%
“…For example, Torimura et al [10] showed that aflibercept can act on VEGFR-1 and -2 in mice. Amin et al [11] and Sergeys et al [12] reported that after intravitreal injection of aflibercept in mice, the leakage of CNV and inflammation were significantly improved [13]. Although the laser-induced CNV mouse model cannot completely simulate the pathophysiological process of CNV in humans, it is a model of acute wound-healing tempo for laser-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Currently, bevacizumab, ranibizumab, and a ibercept are the major anti-VEGF drugs in ophthalmic practice. 12 Accordingly, bevacizumab, [13][14][15][16] ranibizumab, [17][18][19][20][21][22][23] and a ibercept [24][25][26][27][28] are frequently used in experiments with mouse models of retinal vascular diseases. Notably, Ferrara N et al reported that bevacizumab's ability to neutralize VEGF was species speci c and lacking in mice.…”
Section: Introductionmentioning
confidence: 99%